2016
DOI: 10.1111/anec.12376
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Electrocardiographic Analysis of Lead Exposed Workers: An Arrhythmic Risk Assessment Study

Abstract: Lead-exposed workers have a higher risk for atrial and ventricular arrhythmias even without overt cardiac diseases compared with healthy subjects. These workers should be followed closely for adverse cardiovascular outcomes especially arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Some studies have suggested the applicability of Tp-e/QT ratio as a potentially important index of arrhythmogenesis in congenital and acquired channelopathies[23,24]. Furthermore, some studies have evaluated the Tp-e/QT ratio as a potential ECG biomarker for predicting arrhythmia risk and cardiovascular death[25-27]. In the present study, we found an inverse linear association between the Tpe/QT ratio and the E/A ratio.…”
Section: Discussionsupporting
confidence: 70%
“…Some studies have suggested the applicability of Tp-e/QT ratio as a potentially important index of arrhythmogenesis in congenital and acquired channelopathies[23,24]. Furthermore, some studies have evaluated the Tp-e/QT ratio as a potential ECG biomarker for predicting arrhythmia risk and cardiovascular death[25-27]. In the present study, we found an inverse linear association between the Tpe/QT ratio and the E/A ratio.…”
Section: Discussionsupporting
confidence: 70%
“…In 2015, more than 500 Pb-exposed workers (of approximately 800) showed significant elevation in their systolic and diastolic blood pressures in relation to their blood Pb concentrations (mean ± SD, 23.04 ± 11.12 ug/dL) 59 . Increased blood Pb concentrations greater than 35 μg/dL were associated with abnormal electrocardiogram findings in Pb-exposed workers, 60 whereas similar findings were obtained with lower blood Pb levels (30 μg/dL) 61,62 …”
Section: Discussionmentioning
confidence: 84%
“…59 Increased blood Pb concentrations greater than 35 μg/dL were associated with abnormal electrocardiogram findings in Pb-exposed workers, 60 whereas similar findings were obtained with lower blood Pb levels (30 μg/dL). 61,62 Referring to the effect of As exposure on the cardiovascular system, in a previous in-vivo study, cardiotoxicity was induced in Wistar rats with sodium arsenite (5 mg/kg body weight, by mouth) for 4 weeks. Arsenic intoxication significantly increased serum cardiac markers, creatine kinase-MB, lactate dehydrogenase, plasma total cholesterol, triglyceride, phospholipids, free fatty acids, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, and cardiac lipid profile items (total cholesterol, triglyceride, and free fatty acid).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged conduction between atria and ventricle (P-R interval prolongation) has also been reported, among other conduction disturbances that can develop into cardiac arrhythmias (Cheng et al, 1998;Myerson and Eisenhauer, 1963). A related phenomenon, the rates of arrhythmias documented in workers with occupational exposures to Pb 2+ has been estimated, and it is considerably higher than in unexposed control groups (Karakulak et al, 2017). The autonomous innervation of the heart is also affected by Pb 2+ , hence changes in heart rate variability have also been found in employees working under conditions of Pb 2+ exposome (Andrzejak et al, 2004;Madan et al, 2007).…”
Section: Cardiac Effects Of the Lead Exposomementioning
confidence: 99%